2004
DOI: 10.1177/112067210401400108
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Intracranial Hypertension (Pseudotumor Cerebri): Descriptive Epidemiology, Clinical Features, and Visual Outcome in Parma, Italy, 1990 to 1999

Abstract: The incidence rate found in this study is lower than the incidence reported in previous US and Libyan studies. A significant difference in overweight distribution is observed comparing percentage of body weight between US and Parma populations. As overweight and obesity are important factors contributing to IIH development, it is possible that their low percentage in the Parma population may, at least partially, explain the low IIH incidence observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 35 publications
1
29
0
2
Order By: Relevance
“…suggested in the revised diagnostic criteria for pseudotumor cerebri syndrome (Table 2) [Friedman et al 2013]. Other symptoms and clinical signs include dizziness, nausea, reduced memory and concentration and horizontal diplopia due to sixth nerve palsy [Carta et al 2004;Mollan et al 2014;Yri and Jensen, 2015;Yri et al 2012]. Recent studies demonstrated a marked cognitive dysfunction [Kharkar et al 2011;Yri et al 2014a;Zur et al 2015] and indicated that impaired executive function, working memory, processing speed and reaction time remained after normalization of ICP and alleviation of the headache and the visual symptoms [Yri et al 2014a].…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…suggested in the revised diagnostic criteria for pseudotumor cerebri syndrome (Table 2) [Friedman et al 2013]. Other symptoms and clinical signs include dizziness, nausea, reduced memory and concentration and horizontal diplopia due to sixth nerve palsy [Carta et al 2004;Mollan et al 2014;Yri and Jensen, 2015;Yri et al 2012]. Recent studies demonstrated a marked cognitive dysfunction [Kharkar et al 2011;Yri et al 2014a;Zur et al 2015] and indicated that impaired executive function, working memory, processing speed and reaction time remained after normalization of ICP and alleviation of the headache and the visual symptoms [Yri et al 2014a].…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…At time of diagnosis various degrees of visual impairment are present in up to 90% of patients with IIH [Craig et al 2001] and in prior studies an estimated rate of 10-24% progressed to severe and permanent visual impairment [Carta et al 2004;Durcan et al 1988]. Visual loss can occur anytime along the course of the disease but is often insidious and as central vision is spared until late in the course of the illness the visual loss is often asymptomatic until profound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, the incidence of IIH in the general population is 0.5-1.0/100,000 [8,27,28,29,30]. The general population numbers appear to be lower in some Asian countries [31] and higher in Libya [32] and the UK [33].…”
Section: Epidemiology and Obesitymentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Prognosis is variable, with severe visual loss occurring in up to 10% of cases.8 Although few series have specifically evaluated racial differences in IIH, it has been suggested that black patients may have more severe outcomes from IIH.9 -11 The purpose of this study was to compare the characteristics of IIH in blacks and nonblacks.…”
Section: Introductionmentioning
confidence: 99%